Přestavba ručně řízené frézky na CNC frézku - Orság, Petr (Vysoké učení technické v Brně. Fakulta strojního inženýrství, 2016)
V první části práce je uvedená krátká rešerše zabývající modernizací starších strojů a použitých prvků. Jsou zde také uvedeny základní typy frézek. Další část této práce obsahuje popis použité frézky a její parametry. Dále jsou uvedeny výpočty a návrhy vybraných dílů použitých při přestavbě. Vzhledem k charakteru této práce zde nejsou uvedeny výpočty a návrhy všech dílů. Na konci práce se nachází ekonomické zhodnocení přestavby.

In the first part of this thesis, there is a short research dealing with modernization of old-type machines. There is also given a description of main types of milling machines. The next part includes characterization and parameters of the milling machine, that is the subject to the thesis. There are to be found designes and calculations of selected units in the following part. In consideration of the character of the thesis there are not given calculations of all units. The last part deals with economical evaluation.
Conversion of manually controlled milling machine into CNC
Keywords: frézka; automatizace; CNC systém; modernizace; pohon; milling machine; automation; CNC system; modernization; drive